AgQDs employing black box synthetic strategy: photocatalytic and biological behavior - Pansare, Amol V.; Shedge, Amol A.; Chhatre, Shraddha Y.; Das, Debabrata; Murkute, Punam; Pansare, Shubham V.; Nagarkar, Amit A.; Patil, Vishwnath R.; Chakrabarti, S. (Journal of Luminescence, 2019)
This investigation relates FRET, photocatalytic and a biological study of AgQDs which found to be dependent on particle size and capping agent used. Surface of AgQDs was one of the most important factors that govern its activity. AgQDs with BSA binding was systematically studied by fluorescence quenching and electrostatic interaction. AgQDs mainly interacted to site II of BSA, binding distance r evaluated according to the FRET theory and was 4.6 nm for AgQDs, which suggested transfer of energy (non-radioactive) between surface modified AgQDs and biological molecule BSA. The photocatalytic activity of AgQDs for the appreciable degradation of erythrosine dye using Ultraviolet-B light was investigated. AgQDs showed specific antibacterial activity against E. coli bacterial stain. Quantum dots displayed a pronounced and specific activity causing > 50% growth of COLO-205 and MCF-7 human cancer Cells at concentrations < 10(-7 )M. Hence, present black box synthetic protocol of AgQDs could be life science application.
Keywords: AgQDs; Black box; COLO-205; Photocatalytic

Nanocomposite of functional silver metal containing curcumin biomolecule model systems: Protein BSA bioavailability - Shedge, Amol A.; Pansare, Shubham V.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Chakrabarti, S.; Nagarkar, Amit A.; Pansare, Amol V.; Patil, Vishwanath R. (Journal of Inorganic Biochemistry, 2020)
Curcumin, a constituent of Curcuma longa L-Zingiberaceae is used in traditional Indian and worldwide medicine and shows anticancer and antioxidant properties. Curcumin has numerous biological and pharmacological ac-tivities but due to its hydrophobic nature, the major drawback is poor absorption and rapid elimination, rendering curcumin with the tag of a poor biomaterial. Hence, there is a need to develop functional metal containing curcumin model systems (FMCCMS) as a metallo-biomolecule to enhance the bioavailability of curcumin. We designed the interaction of silver metal ion with curcumin to form curcumin-silver nanocomposite (CURC-AgNCP) via ultrasonic synthetic route. Formations of FMCCMS were characterized by spectroscopic techniques. The crystalline face-centered cubic pattern and particle size of the nanocomposite was evaluated using X-ray diffraction and high-resolution transmission electron microscopy. The bonding of silver metal to curcumin was confirmed by X-ray photon spectroscopy. Interaction of the nanocomposite with bovine serum albumin (BSA) protein was performed using excitation, emission, and circular dichroism spectroscopy. In binding interaction of BSA, the negative value of Delta S degrees (-358.04 J mol(-1) K-1) and Delta H degrees (-129.42 KJ mol(-1)) demonstrates the hydrophilic nature of the nanocomposite. The binding distance r evaluated according to the Forster resonance energy transfer theory and was 4.69 nm for CURC-AgNCP, which suggested non-radiative transfer of energy between CURC-AgNCP and BSA. The role of FMCCMS metallo-biomolecule CURC-AgNCP in medicine for cancer activity can have immense importance and hence we performed Sulphorhodamine B based in-vitro cytotoxicity assay on human breast cancer Michigan Cancer Foundation-7 cell line.
Keywords: Ag-based CURC biomaterials; Breast cancer; Metal in medicine; Metallobiomolecules; Nanocomposite